2021
DOI: 10.21468/scipostphys.10.5.109
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of coarsening and mean field relaxation in the long-range Ising chain

Abstract: We study the kinetics after a low temperature quench of the one-dimensional Ising model with long range interactions between spins at distance rr decaying as r^{-\alpha}r−α. For \alpha =0α=0, i.e. mean field, all spins evolve coherently quickly driving the system towards a magnetised state. In the weak long range regime with \alpha >1α>1 there is a coarsening behaviour with competing domains of opposite sign without development of magnetisation. For strong long range, i.e. 0<\alpha <10<α<1, w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…In this paper we have considered the phase-ordering kinetics of the one-dimensional Ising model with long-range interactions decaying with distance as J(r) ∝ r −α , with α ≤ 1. In a previous paper [6] it was shown that, in this process, the statistical non-equilibrium ensemble splits into two different kinds of trajectories, those which develop coarsening domains, and those which do not so and behave similarly to mean field. Restricting the observation on the former ones, in the present study we have performed numerical simulations to compute the probability distribution p α (s, t, N) of the domain sizes, from which the growth-law of the average domains size s α (t, N) can be inferred.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this paper we have considered the phase-ordering kinetics of the one-dimensional Ising model with long-range interactions decaying with distance as J(r) ∝ r −α , with α ≤ 1. In a previous paper [6] it was shown that, in this process, the statistical non-equilibrium ensemble splits into two different kinds of trajectories, those which develop coarsening domains, and those which do not so and behave similarly to mean field. Restricting the observation on the former ones, in the present study we have performed numerical simulations to compute the probability distribution p α (s, t, N) of the domain sizes, from which the growth-law of the average domains size s α (t, N) can be inferred.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous article [6] we have shown that for α ≤ 1, the presence of configurations with coarsening domains is a stochastic phenomenon which may occur (or not), depending on the different dynamical realisations, with a given probability π α (t, N) plotted in Fig. 1 and defined as the fraction of trajectories that at time t = 1 presents at least two domains.…”
Section: The Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…In the first case, sometimes denoted as strong long-range regime, some fundamental physical properties, such as additivity, are spoiled, causing major differences with respect to the kinetics of the short-range case. In particular, it was shown [19] that, at least in d = 1, a mean-field like dynamics dominates in the thermodynamic limit L → ∞. In this case, spins tend to align with the sign of global magnetization, the symmetry is soon broken, and metastable states such as those described before for short-range systems cannot be sustained.…”
mentioning
confidence: 92%